Concurrency, Compositionality, and Correctness Essays in Honor of Willem-Paul de Roever - Dams, Dennis; Hannemann, Ulrich; Steffen, Martin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This Festschrift volume, published in honor of Willem-Paul de Roever, contains 19 detailed papers written by the friends and colleagues of the honoree, all eminent scientists in their own right. These are preceded by a detailed bibliography and rounded off, at the end of the book, with a gallery of photographs. The theme under which the papers have been collected is Concurrency, Compositionality, and Correctness, reflecting the focus of Willem-Paul de Roever's research career. Topics addressed include model checking, computer science and state machines, ontology and mereology of domains, game theory, compiler correctness, fair scheduling and encryption algorithms.
A Bibliography of Willem-Paul de Roever -- Playing Savitch and Cooking Games -- Compositionality: Ontology and Mereology of Domains -- Computer Science and State Machines -- A Small Step for Mankind -- On Trojan Horses of Thompson-Goerigk-Type, Their Generation, Intrusion, Detection and Prevention -- Explicit Fair Scheduling for Dynamic Control -- Synchronous Message Passing: On the Relation between Bisimulation and Refusal Equivalence -- Reasoning about Recursive Processes in Shared-Variable Concurrency -- Formal Semantics of a VDM Extension for Distributed Embedded Systems -- A Proof System for a PGAS Language -- Concurrent Objects à la Carte -- On the Power of Play-Out for Scenario-Based Programs -- Proving the Refuted: Symbolic Model Checkers as Proof Generators -- Meanings of Model Checking -- Smaller Abstractions for ?CTL* without Next -- Timing Verification of GasP Asynchronous Circuits: Predicted Delay Variations Observed by Experiment -- Integrated and Automated Abstract Interpretation, Verification and Testing of C/C++ Modules -- Automated Proofs for Asymmetric Encryption -- Counterexample Guided Path Reduction for Static Program Analysis.
Keywords: Computer science; Software engineering; Computer software; Logic design; Computer Science; Logics and Meanings of Programs; Computation by Abstract Devices; Mathematical Logic and Formal Languages; Algorithm Analysis and Problem Complexity; Software Engineering; Programming Languages, Compilers, Interpreters